The ASCRS manual of colon and rectal surgery - Wexner, Steven D.; Hull, Tracy L.; Roberts, Patricia L.; Saclarides, Theodore J.; Senagore, Anthony J.; Stamos, Michael J.; Steele, Scott R.; Beck, David E. (Springer New York, 2014)
The ASCRS Manual of Colon and Rectal Surgery, Second Edition is designed to provide a rapid access pocket reference for residents, fellows, private clinicians, and allied health professionals caring for patients with colorectal surgical diseases. The Manual, abstracted from the ASCRS Textbook of Colon and Rectal Surgery, Second Edition, is intended to impart succinct, clinically relevant information for daily patient care. The chapters take an evidence-based approach and many provide ASCRS practice parameters. The contents are presented consistently, with concise overviews of the most clinically relevant topics. The disease chapters discuss etiology, anatomic considerations, patient evaluation, lab results, imaging, diagnosis and treatment. The surgical chapters address these same issues, in addition to discussion of minimally invasive versus open techniques, possible complications, and perioperative care. The Manual also includes anatomical and technique drawings, operative photos and algorithms.   Concise yet comprehensive, The ASCRS Manual of Colon and Rectal Surgery, Second Edition is very useful for physicians and researchers dealing with diseases of the colon and rectum.